MODERNIZATION OF THE RUSSIAN ECONOMY - Andrey P. Garnov; Viktoriya Yu. Garnova (Вестник Российского экономического университета имени Г. В. Плеханова)
The main function of innovation system at the modernization stage is founding conditions for economic growth on the basis of fast development of own and imported overseas technologies. In this connection the article shows that the announced policy of import-substitution requires a whole set of adequate conditions in the field of finance, scientific and personnel support and availability of free industrial capacities. With regard to the real situation meeting the requirements of import-substitution policy in the short term is very difficult. As for long-term prospects, success depends (based on the experience of fast developing economies) on deepening cooperation with world research-technological and industrial complexes. Based on the analysis the authors formulated a number of steps which could provide the effective import of technologies.